DYSTOPIAN OPPRESSION AND MATERNAL RESISTANCE IN LEILA (2019) - Basumatary, Dwitun (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Netflix’s adaptation of Leila, based on Prayaag Akbar’s novel, presents a haunting vision of a near-future India where religious authoritarianism and caste segregation dictate every aspect of life. This research explores how the series portrays oppression, surveillance, and resistance, particularly through the lens of maternal struggle. Using feminist literary theory and postcolonial critique, the study examines the dystopian world of Aryavarta and its mechanisms of control. It argues that Leila serves as both a warning and a reflection of contemporary societal anxieties. The research employs a comparative textual analysis methodology, examining the novel and its adaptation to assess narrative shifts and thematic emphasis.